Causes and Initial Efffects of the Spanish Organic Law 1/2009 Reforming the Principle of Universal Jurisdiction in Spain (Spanish Yearbook of International Law, 2012)
For some years now, Spain has been in the vanguard of the court battle against international crime, particularly since the Pinochet case. The country’s progressive legislation about universal justice and the interpretation of such principle by the Spanish Constitutional Tribunal in the Guatemalan case (and later, in the Falung Gong case) are the reasons behind its exceptional role in the application of International Criminal Law. However, the exercise of this right entitled to the victims, when directed against the citizens of one of the permanent U. N. Security Council country members, has precipitated a legal reform in the end. It is undeniable that these States, and particularly the U. S. and China, have put the Spanish political class under a great deal of pressure for the cases under trial at the Spanish National Court, such as the Guantanamo case, the Bush Six, the CIA case, and the Couso, Tibet and Falung Gong cases. Consequently, Spain passed the Organic Law 1/2009 that restricts the scope of universal jurisdiction in the country. The reforms in the Spanish Parliament and the following content amendment of the legislative reform of Article 23.4 of LOPJ point to the victory of the real-politik over the efffective prosecution of the gravest international crimes. The presence of the accused in Spanish territory, the introduction of the principle of establishing standing to sue the defendant, or the requirement of relevant “connecting links with Spanish interests” are the new obstacles that stand between the Spanish courts and their capacity to try international crimes. Likewise, the ratifĳication of the inversion of the principle of complementarity of jurisdiction of the International Criminal Tribunal with regard to the Spanish courts, plus the danger of the stay of proceedings prior to the opening of a criminal trial in another court limit further the access to justice. The efffects of these new legal requirements on the cases of the Spanish National Court were not slow in coming. Not only the new complaints against the Burma’s military Junta have been disallowed, but it has also afffected those cases already under investigation, which have been dismissed on the grounds of lack of connections with national interests. This is why cases such as the Tibetan case have died out after the legal reform, whereas others (Bush’s Administration’s legal advisors case) will withstand until the connecting link to the country’s interest is assessed and, particularly, until the role played by the Spanish Government and the coordination of the Prosecutor’s offfĳice with the U. S. Embassy in Madrid is evaluated. In any event, the fĳirst provisional assessment of this legal reform clearly indicates a shortfall in the victims’ right to justice and redress, and a policy to favour impunity for the most powerful.